E-learning readiness among medical educators in Universiti Sains Islam Malaysia - Salleha Khalid; Tengku Amatullah Madeehah Tengku Mohd; Khadijah Hassanah; Muhammad Shamsir Mohd Aris; Khaironi Yatim; Mohd Mokhtar; Suhaila Sanip (Science Publication, 2024)
Volume 11 No. 1